The effects of beetroot supplemmentation on heart rate, blood lactate, and exercise performance in trained athletes - Wax, B.; Mayo, J.; Frick, S.; Landry, A.; Harris, M.; Lyons, B. (The Journal of Strength and Conditioning Research, 2021)
The release of nitrates, which elicits vasodilation within the blood vessels, may facilitate muscular performance, especially when high intensity work is involved. Beetroot is purported to increase blood flow and, consequently, oxygen and nutrient delivery to the working muscles during exercise performance. However, the ergogenic benefit of beetroot during circuit performance has not been established. Purpose: The purpose of this study was to investigate the effects of beetroot supplementation on blood lactate, heart rate, and muscular performance in trained athletes. Methods: In a double-blind, randomized, crossover design, heart rate dynamics, blood lactate, body composition, and resistance performance were assessed before and after supplementation. Ten males (age = 29.3 ± 2.4 years, mass = 85.9 ± 10.6 kg, height = 69.80 ± 4.05 cm, body fat = 16.2 ± 4.7%) and 6 females (age = 32.3 ± 4.4 years, mass = 65.2 ± 3.6 kg, height = 61.6 ± 2.05 cm, body fat = 28.5 ± 5.7%) ingested either beetroot powder or cellulose powder (CP) capsulized in gelatin capsules, over a 14 day period prior to a selected circuit training protocol (3 rounds of squats, overhead press, and 9 pullups). A 7-day washout period divided treatment conditions. Results: Resting and post exercise heart rate between females and male were ascertained. There was no significant difference between treatment groups for pre exercise heart rate; however, beetroot ingestion revealed a lower post exercise heart rate (p = 0.049). There was no significant difference in treatment A (placebo) and treatment B (beetroot supplementation) for body composition, and post exercise blood lactate. There was a significant difference in treatment B (beetroot supplementation) in exercise performance time (t = 2.349, p = 0.047). Conclusions: The consumption of beetroot supplementation improved whole body, high intensity workout performance with a lower post exercise heart rate in trained athletes. Practical Applications: Our data suggest that chronic supplementation of beetroot powder may provide some ergogenic benefits to trained athletes.